Penyelesaian Perkara Pidana Medik Bagi Tenaga Medis dalam Hukum Kesehatan: Studi Perbandingan Hukum di Indonesia, Belanda dan Britania Raya - Delviana, Nurmaida; Lumbuun, T. Gayus; Rokhmat, Rokhmat; P.H., Agustinus; Suswantoro, Tri Agus (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The realization of a country's national development goals is a measure of a country's success, namely through law enforcement and a good health index of its citizens in that country. This research specifically discusses the enforcement of health law where it is not only looked at from the perspective of the laws that apply in Indonesia, but a comparison is made of the resolution of problems in health law that arise as a result of actions carried out by medical personnel that are related to their competence (unprofessionalism: medical errors in the form of omission, negligence, and/or intentional) which resulted in lawsuits and lawsuits based on legal provisions in the Netherlands and the United Kingdom. The research method used is prescriptive analysis and qualitative approach data analysis. The research results show that the settlement of lawsuits, especially the settlement of medical cases in Indonesia, the Netherlands and the United Kingdom, is currently still within the jurisdiction of the general courts; in Indonesia it is regulated in Law Number 2 of 1986 concerning General Courts along with amendments to the two Laws in Law Number 49 of 2009; in the Netherlands it is regulated in the Judicial Organization Act, the Judicial Sector (Funding) Decree of 2005, and the Constitution of the Kingdom of the Netherlands 2002; whereas in the United Kingdom it is based on the Criminal Procedure Rules 2020 and Criminal Practice Directions 2023